Pembelajaran pasca pandemi covid-19 di Sastra Jerman Universitas Negeri Malang - Putri, Oryza Kumala; Wijayati, Primardiana Hermilia (Fakultas Sastra, 2023)
Abstrak: This paper is the result of research on the phenomenon of learning loss caused by a lack of interaction during online learning for students of the Department of German Language Education, State University of Malang. The purpose of this research is to describe learning loss due to lack of interaction of German Language Education students of State University of Malang during online learning. Learning loss is a phenomenon where students experience a decrease in knowledge. This research uses a descriptive method with a quantitative approach, then the data collection technique uses Purposive Random Sampling with a research sample of 2019-2021 batch students, each of which consists of three batches which will be taken randomly. Data were obtained using a questionnaire distributed using Google Form. Data analysis in this study used descriptive statistical techniques. The results showed that most students of the German Language Education Department experienced the phenomenon of learning loss due to lack of interaction during online learning during the COVID-19 pandemic. Kata Kunci: learning loss, interaction